Health insurance and quality and efficiency of medical care for patients with acute myocardial infraction in tertiary hospitals in Shanxi, China: a retrospective study. (October 2016) - Lin, Xiao Jun; Tao, Hong Bing; Cai, Miao; Cheng, Zhao Hui; Li Wang, Man; Xu, Chang; Lin, Hai Feng; Jin, Li
Abstract: Background: Previous studies have shown that health insurance type affects patient outcomes, but empirical research on the effect of health insurance on quality and efficiency of care in China is scarce. This study aimed to determine whether there are health insurance-related differences in hospital care for acute myocardial infraction. Methods: Patients with a principal diagnosis of acute myocardial infraction were identified from inpatient discharge records of 27 tertiary hospitals in Shanxi, China from September 1, 2013, to October 31, 2014. Patients were classified into four health insurance categories: Urban Employee Basic Medical Insurance (UEBMI), Urban Residents Basic Medical Insurance (URBMI), the New Rural Cooperative Medical Scheme (NCMS), or uninsured (out-of-pocket). The outcomes of interest were in-hospital mortality, length of stay, and total cost. Multilevel logistic regression was applied for in-hospital mortality, and multilevel linear regression for log transformed LOS and total cost. All models were adjusted for patient and hospital characteristics. Limited information from patient medical records was extracted from a database and all records were anonymised. As such, no ethical approval was required for this study. Findings: We analysed records for 9075 patients. Compared with UEBMI group, in-hospital mortality was significantly lower for NCMS group (OR 0·613 [95% CI 0·438–0·859]) and uninsured group (0·477 [0·281–0·810]). Excluding patients who died during hospitalisation, compared with UEBMI group length of stay was shorter in the URBMI (coefficient of variable, −0·074 [95% CI −0·115 to −0·034]), NCMS (−0·116 [–0·139 to −0·093]) and uninsured (−0·146 [–0·177 to −0·114]) groups and total cost was lower in the URBMI (−0·067 [–0·130 to −0·004]), NCMS (−0·118 [–0·154 to −0·082]) and uninsured (−0·115 [–0·165 to −0·066]) groups. Interpretation: For patients hospitalized for acute myocardial infarction, health insurance type is significantly associated with quality and efficiency of care under current health policies in Shanxi, China. The underlying mechanism justifying this association should be explored further. Funding: None.